IEEE 54th Vehicular Technology Conference. VTC Fall 2001. Proceedings (Cat. No.01CH37211)
DOI: 10.1109/vtc.2001.957195
|View full text |Cite
|
Sign up to set email alerts
|

Frequency shift based multiple access interference canceller for DS-CDMA systems

Abstract: Abstract-The cyclostationary properties of Direct Sequence Spread Spectrum signals are well known. These cyclostationary properties imply a redundancy between frequency components separated by multiples of the symbol rate. In this paper we present a Multiple Access Interference Canceller that explores this property and applies to UMTS-TDD. This frequency domain Canceller acts in the spreaded signal in such way that minimizes the interference and noise at its output (Minimum Mean Squared Error Criterium). The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The conversion method between redundant bands expressed by (14) is the base of the FSC and represents a generalization of the technique developed in [5] where the use of a fixed spreading factor resulted a scalar transformation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…The conversion method between redundant bands expressed by (14) is the base of the FSC and represents a generalization of the technique developed in [5] where the use of a fixed spreading factor resulted a scalar transformation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In the present paper we extend the work of [5] to include the general situation of UMTS-TDD where users with different spreading factors can coexist in the same time slot. This enables the transmission of services with different rates by varying the spreading factor, but the structure of the spreading (channelization times scrambling) in UMTS-TDD lead to codes that extend over several symbols.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work [5] the Frequency Shift Canceller (FSC) was defined and implemented for a fixed spreading factor. The results have shown that considerable improvement is achieved against the RAKE and the FSC even outperforms the PIC for moderate to high values of E b /N 0 .…”
Section: Introductionmentioning
confidence: 99%